My iPad for Seniors, 8th Edition - Miller, Michael (Que, 2020)
Covers all iPads running iOS 14. Easy, clear, readable, and focused on what you want to do. Full-color, step-by-step tasks walk you through getting and keeping your iPad working just the way you want. Learn how to: Wirelessly connect to and browse the Internet, at home or away Video chat with your friends using FaceTime over Wi-Fi or cellular Make your iPad easier to use if you have trouble seeing or tapping the screen Use Siris voice commands to control your iPad and find useful information Communicate with friends and family via email, text messaging, and FaceTime video chats Shoot, share, and view photos and videos Listen to streaming music and watch streaming movies and TV shows online Find locations and get directions using the new Maps app Use iCloud to store and share your photos and other important data online Troubleshoot common iPad problems.